Penerapan Kombinasi Model Pembelajaran Tipe Numbered Head Together dengan Problem Based Learning untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas X PMIA 1 SMAN 3 Banjarmasin Pada Konsep Perubahan Lingkungan - Noorhidayati Noorhidayati; Heny Mawarni; Hardiansyah Hardiansyah (Program of Biology Education, Universitas Lambung Mangkurat, 2019)
Learning is a basic process of formal education in a limited scope and can determine the quality of the next world of education. Based on the results of interviews, it is known that the activity and student learning outcomes on the concept of Environmental Change in the class are still relatively low. The research aims to improve the activities and learning outcomes of Class X PMIA 1 SMAN 3 Banjarmasin academic year 2016/2017 on the concept of Environmental Change, as well as describe student responses through the application of a combination of NHT and PBL type learning models in their learning. This Classroom Action Research consists of two cycles, each cycle consists of 2 meetings. The subjects of this study were all 36 students of class X PMIA 1 SMAN 3. The results showed: Student activity during the learning process from cycle I to cycle II increased from an average of 82.31 to 90.02 with a fixed category (good). Cognitive learning outcomes of students' products during the learning process increased, in the first cycle 38% to the second cycle to 92.5% of all students who achieved a score of 76. Cognitive learning outcomes during the learning process increased from the first cycle of 72.77 with a sufficient category good to 82.28, in the second cycle with good category. Student responses were positive, with details of 30% of students strongly agreeing, and 60% of students agreeing, while the negative response was 10%.